2017
DOI: 10.1007/s00018-017-2686-7
|View full text |Cite
|
Sign up to set email alerts
|

CD4 and CD8 T lymphocyte interplay in controlling tumor growth

Abstract: The outstanding clinical success of immune checkpoint blockade has revived the interest in underlying mechanisms of the immune system that are capable of eliminating tumors even in advanced stages. In this scenario, CD4 and CD8 T cell responses are part of the cancer immune cycle and both populations significantly influence the clinical outcome. In general, the immune system has evolved several mechanisms to protect the host against cancer. Each of them has to be undermined or evaded during cancer development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
283
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(325 citation statements)
references
References 240 publications
8
283
0
5
Order By: Relevance
“…37,38 Studies have shown that the recognition of neoepitopes by endogenous T cells may elicit protective immune responses without being affected by central T cell tolerance, making neoantigens an ideal target for cancer immunotherapy. 4,39,40 Neoantigen vaccines can be developed using different strategies. Premanufactured vaccines may be developed to target neoepitopes related to recurrent somatic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Studies have shown that the recognition of neoepitopes by endogenous T cells may elicit protective immune responses without being affected by central T cell tolerance, making neoantigens an ideal target for cancer immunotherapy. 4,39,40 Neoantigen vaccines can be developed using different strategies. Premanufactured vaccines may be developed to target neoepitopes related to recurrent somatic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…CD4+ and CD8+ T lymphocytes are the main players for secondary immune response against tumor. (Hung et al, ; Ostroumov, Fekete‐Drimusz, Saborowski, Kühnel, & Woller, ) Therefore, tumors' sections were stained with anti‐CD4 and anti‐CD8 antibodies to identify these two kinds of cells recruitment to the tumor site by IHC (Figure B). CD4 and CD8 are the well‐known markers of T helper and cytotoxic T lymphocyte cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…CD4+ and CD8+ T lymphocytes are the main players for secondary immune response against tumor. (Curiel et al, ; Hung et al, ; Ostroumov et al, ) Therefore, tumors' sections were stained with anti‐CD4 and anti‐CD8 antibodies to identify these two kinds of cells recruitment to the tumor site by IHC (Figure B). Significant increase of both CD4+ and CD8+ T lymphocytes cells recruitment to the tumor site was detected at the Spirulina extract treated mice in comparison with PBS and control group.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, M1-like macrophage induction correlates with better control of tumor growth and also stimulation of anti-tumor protective adaptive T cells [39,40], in particular with CD4 + TH1 cells, which are key activators in the priming phase, and CD8 + T cytolytic cells in the rejection effector response against tumor [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%